Mengelola Konflik di Tempat Kerja: Apa dan Bagaimana? - Imas Maesaroh (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2021)
An organization cannot avoid conflict. Individual characteristics and the types and pressures of work can lead to conflict in organizations. Conflict occurs when the desires of two or more people are incompatible. Likewise, the will of one organization that is different from another can also lead to conflict. Some individuals or groups can benefit from confrontation if it is appropriately resolved. Conflict management refers to handling disputes or disagreements constructively and effectively. Conflict management aims to minimize negative consequences and maximize positive outcomes for all parties involved. Effective conflict management involves identifying the root causes of conflict, fostering open communication, and implementing strategies to deal with the problems. Successful conflict management can lead to improved relationships, increased productivity, and increased organizational performance. However, ineffective conflict management can lead to prolonged conflicts, damaged relationships, and reduced morale. Therefore, understanding and practicing practical conflict management skills is essential for individuals and organizations to succeed in today's complex and interconnected world.